PERKAWINAN ANTAR WANGSA : ANALISIS PERWARISAN DALAM ADAT BALI (Kajian Masyarakat Aktif Bali) - A.A. Istri Ngurah Dyah Prami; Nazrina Zuryani (Prodi Sosiologi FISIP Universitas Teuku Umar, 2016)
Adat regulations in Bali is not only contradict dualism of men and women as purusa pradana, it gives the mipil (registration at village level) to men. Besides this patriarchy system, in marriage especially there is alsowangsa influence; they are the groups of Brahmin, Ksatria, Waisya and Sudra. Each group as Etzioni[1] (1968)suggests taking up different positions in Balinese active society. They are bounded in patterns of banjar with Awig-awig (written agreement), in familial (menyama braya) or clan patterns, and complex marriage engagements. Ategen asuwun is a newly concept of inheritance (2 parts for sons and 1 part for daughters) based on marriage engagement for contemporary Balinese adat regulations. Wangsa system in adat marriage is the impetus of Balinese women’s problems. Marriage is displacing women as limited ninggal kedaton from theirfathers temple to their husband’s temple. Social construction in society has prohibited a high caste/wangsa woman to marry lower caste man (nyerorod marriage). This wangsa system has limited Balinese women’s right to inherit even they are in the same clan and wangsa. As a result, never marriage woman is one of the choise to get her inheritance. In the anuloma marriage where as a high caste man marry a lower caste woman, the concept of limited ninggal kedaton is still taking place and modern familial system has given daughers the one part of tatadan inheritance. However, the anomaly is given to a newly religious converted woman by marriage where is full ninggal kedaton gives no inheritance at all to her. Key words: Balinese women, Intercaste marriage, Inheritance rights[1]Lihat bab 15 pada buku Margareth M Poloma, Sosiologi Kontemporer (Rajawali Pers, 2013) hal 352-373.